Examining AI Guidelines in Canadian Universities: Implications on Academic Integrity in Academic Writing - Marcel, Faith; Kang, Phoebe (Discourse and Writing/Rédactologie, 2024)
Academic integrity is a crucial aspect of higher education that fosters intellectual honesty and upholds the principles of fairness and trustworthiness (Stoez & Eaton, 2020; Kang, 2022; Eaton, 2022). As the introduction and integration of artificial intelligence (AI) technologies becomes increasingly prevalent in educational settings, it is imperative to examine how Canadian universities are addressing the implications of AI on academic integrity (Eaton, 2022; UNESCO, 2023). This study aimed to examine the existing AI guidelines and policies developed and implemented by Canadian universities and analyze their alignments and gaps in relation to their academic integrity policies, particularly in the domain of academic writing in Canadian higher education contexts. In this research study, sixteen Canadian universities were selected for document analysis, and through an examination of their existing polices and guidelines on AI, results revealed insights into both challenges and opportunities for faculty, students and stakeholders around teaching academic writing while upholding academic integrity in higher education.